Theoretical Analysis of AlxGa1-xAs/GaAs Graded Band Gap Solar Cell - Alshekhli, Belal A (Al-Nahrain Journal of Science, 2018)
The graded band gap AlxGa1-xAs/GaAs solar cell model has been proposed. This model consists of graded compositions material in the surface layer extending from y=0 to y=D, and uniform band gap from y=D to y=L. The model simulates the absorption, generation, current density, spectral response and the solar efficiency generated from the solar spectrum. These photovoltaic parameters have been calculated by a GRAD computer program. Electric field, mobility and diffusion length of holes gradient are assumed constant in the model to get an analytical solutions. The photovoltaic parameters, obtained from the model, are Jsc =33 mA/cm2, Voc= .91 V, FF= .87 and η= 31 %. The conversion efficiency is considered high as compared with other similar models.